The Health Status of Dentists Exposed to Mercury from Silver Amalgam Tooth Restorations - Duplinsky, Thomas G.; Cicchetti, Domenic V. (International Journal of Statistics in Medical Research, 2012)
The authors employed pharmacy utilization data to evaluate the health status of a representative sample of 600 dentists, matched to control subjects, for gender, age, geographical area, and insurance plan structure. Dentists demonstrated significantly more prescription utilization of specific illness medications than did Controls, for the following disease categories: Neuropsychological, Neurological, Respiratory, and Cardiovascular. The greater majority of pediatric and general practice dentists still use mercury amalgam restorations. This places them at greater risk than the general population for those disorders, as well as threatening the future health of America’s children and adults who continue to receive silver amalgam restorations.